Applications of Ionic Liquids for the Biochemical Transformation of Lignocellulosic Biomass into Biofuels and Biochemicals : A Critical Review - Nazife Isik Haykir; Sharareh Harirchi; Taner Sar; Mukesh Kumar Awasthi; Mohammad J. Taherzadeh; Shikh Mohd Shahrul Nizan Shikh Zahari (Elsevier, 2024)
Indexed by WOS/Scopus/ERA